PENINGKATAN KAPASITAS TIM PENDAMPING KELUARGA (TPK) MELALUI PROGRAM SUCCESS KALTARA DI DESA TIDENG PALE KABUPATEN TANA TIDUNG - Gusriani, Gusriani; Hartika, Andi Yuniarsy; Umami, Nurrahmi; Alfianur, Alfianur; Retnowati, Yuni; Padlilah, Rahmi (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2023)
The Capacity Building Program for Tim Pendamping Keluarga (TPK) in Tideng Pale Village, Tana Tidung Regency, was conducted from September 5-8, 2023, as part of the Success Kaltara initiative to reduce stunting rates. The program aimed to enhance TPK's knowledge and skills in early stunting detection, anthropometric measurement, and balanced nutrition education. Methods included initial coordination with relevant parties, administrative preparation, training implementation using presentations, demonstrations, simulations, and interactive activities, as well as activity evaluation and documentation. The program results showed significant improvements in participants' knowledge and skills. Pre and post questionnaire evaluations indicated an increase in knowledge from 60% to 90% in early stunting detection, anthropometric measurement skills from 55% to 85%, and understanding of balanced nutrition from 50% to 80%. Documentation of training results and follow-up plans ensured the program's sustainability. Challenges such as limited access and network issues were addressed with appropriate strategies, including selecting easily accessible locations and support from related partners